Методика преподавания информатики и информационных технологий на основе интерактивных методов - Кунназаров, О. (SCIENCE and SOCIETY, 2025)
The article analyzes interactive teaching methods as a tool for enhancing the quality of education in the field of computer science. The aim of the study is to assess the impact of these methods on students’ material comprehension. Surveys, observation, and exam analysis were used. The results show that interactive methods, including project-based activities and role-playing games, contribute to improved academic performance, critical thinking, and collaboration skills. The conclusion emphasizes the importance of implementing interactive learning and provides recommendations for teachers.